Management and surgical treatment of parathyroid carcinoma: a 6-year experience of a single centre of endocrine surgery unit - Laforgia, Rita; Tomasicchio, Giovanni; Cavalera, Federica; Sblendorio, Maria; Spadone, Annamaria; Anelli, Ferdinando Massimiliano; Lobascio, Pierluigi; Marzaioli, Rinaldo; Panebianco, Annunziata; Pezzolla, Angela (Frontiers in Endocrinology, 2023)
Background Parathyroid carcinoma (PC) affects 0.1-0.3% of the general population and represents the rarest malignant neoplasms among endocrinological diseases, comprising less than 1%. The best therapeutic treatment and management methods are still debated in the literature. The aim of this study is to evaluate the management and surgical treatment of parathyroid carcinoma after 6 years of enrolment with the Endocrine Surgery Unit of the University Hospital of Bari. Materials and Methods A retrospective observational study was carried out using a prospectively maintained database of patients affected by primary hyperparathyroidism between January 2017 and September 2022. Consecutive patients over 18 years old with a final histopathological finding of PC were included in the study. Patients with secondary or tertiary hyperparathyroidism, parathyroid hyperplasia, and parathyroid adenoma were excluded. All patients underwent follow-up every 6 months for the first 2 years, and annually thereafter. Results In this study, 9 out of 40 patients affected by hyperparathyroidism were included; 6 (66.6 %) were female and 3 (33.3%) were male patients, with a median age of 59 years (IQR 46-62). None had a family history of PC. No mortality was recorded while the incidence of recurrence was 22.2 %, with a disease-free survival of 8 and 10 months. Parathyroidectomy was performed in five patients, while four patients underwent parathyroidectomy with concurrent thyroidectomy for thyroid goitre. No intraoperative complications were recorded. Open parathyroidectomy was performed with a mini-cervicotomy in seven patients, while two patients underwent robotic surgery. All patients were discharged on the second postoperative day. Conclusion PC represents a great challenge in terms of preoperative diagnosis, management and treatment. A surgical approach represents the first best option for PC in referral endocrine surgery units. The early identification of risky patients should be the dominant goal to plan an appropriate therapy and to perform adequate en bloc surgery.